The Jurisprudential Origin of the Formal Mortgage: A Comparative Study - Al Masri, Na'em Samara (Journal of Islamic and Religious Studies, 2022)
Mortgage is one of the most important tools of credit in debt. A new form of the mortgage that wasn't known to the ancient jurists emerged, and it is the official or real estate mortgage. A new form of the mortgage that wasn't known to the ancient jurists emerged. Such form became the prevalent in contemporary documentation. The main objective of research is to answer the question: Is the official research in its contemporary form permissible according to the Islamic religion? The main objective of this system also is to clarify the provisions of Islamic Sharia regarding mortgage and its ways. There are many previous studies that dealt with the issue of mortgage, but most of them did not follow the approach they were aiming at, but they briefly explained the opinion of contemporary jurists only. The comparative analytical inductive method was adopted. The research was divided into an introduction that included the research problem, questions, objectives, and the adopted approach, and three sections: First: Definition of mortgage, its legitimacy, and types. Second: The jurisprudential adaptation of the formal mortgage. Third: The most important Islamic legal rulings for mortgage and ways of dealing. Finally, the conclusion included the findings of formal mortgage that don’t contradict the provisions of mortgage known to jurists of four doctrines in clarifying the issue of mortgage.